Praktik Baik Pembelajaran dalam Jaringan (Online Learning) di SMK N 32 Jakarta selama Masa Pandemi - Maya Oktaviani; Ayu Friditya Wulaningrum; Dewi Firliyanti; Febryanti Peedro Widyasari; Kantoni Kantoni; Ratu Sheila Azzahra; Rizky Lusiana (Universitas Al Azhar Indonesia, 2022)
The Covid-19 pandemic has led to policy changes in the education sector. Face-to-face learning activities turned into distance learning or online learning. However, in practice, teachers and students often encounter problems so that learning becomes less than optimal. This study aimed to analyse the effectiveness of online learning during the pandemic from students' points of view. The research was conducted at SMK N 32 Jakarta in April 2021 with qualitative research methods. The population used in this study were students of SMK N 32 Jakarta, with a sample of 50 students who were selected using the quota sampling technique. According to students, the research results indicate that the online learning undertaken during this pandemic has been going well because the material and explanation received are pretty straightforward, making it easier to understand the learning material. A total of 67.62% of respondents felt that the material and explanations received were well understood.Keywords - Online learning, Distance learning, Learning proces